A Palimpsest Reading Between the Past, the Present and the Future: Kayseri Sahabiye District as a Case - Güler, Fatma Büşra; Durak, Selen; Vural Arslan, Tülin (ICONARCH International Congress of Architecture and Planning, 2017)
With the impact of globalization, the spatial transformation of cities has gained momentum and it becomes difficult to read the continuity between the past, the present and the future of the cities. Recently, in Turkish cities, urban environments that bear the traces of history are faced with transformation. In the last decade, transformation is realized through grand regeneration projects which are perceived as a panacea for modernization of urban environments. However, during the implementation process, projects including many building lots; even sometimes a whole district are redesigned by disregarding the existing urban pattern such as street networks, existing architectural characteristics, daily life practices, etc. In Kayseri, Sahabiye District that is located within the city center, is on the agenda with an urban regeneration project in recent years. The area that takes its name from historic Sahabiye Madrasah, is one of the first Modernist housing examples of the Republican ideology. With the influence of housing policies in Turkey, the district is in a process of continuous transformation and re-existence. This study aims to discuss the issues of urban identity and housing through analyzing Sahabiye District, which can be read as a palimpsest between the past, the present and the future. The transformation process of the district has been grouped into five phases as the Pre-Republican Period, Early Republican Period (1923-1950), the Period between 1950-1980, the Period between 1980-2000, and finally the Period from 2000 until today. Visual materials such as photographs, maps and plans have been used in order to document the past and the present situation of an urban pattern which is going to disappear in the near future.